Building back better after the COVID-19 pandemic - Jaramillo, Miguel (2021)
In this policy-oriented paper, we provide a pre- and post-pandemic socioeconomic analysis of Peru, along with a financially sustainable five-year Building Back Better recovery plan, which emphasizes the urgency of addressing some of the country’s structural weaknesses. We underscore the importance of public investment for this effort, but widen the focus to include current public expenditure, in order to take steps towards building a more universal social protection system. We show that this also contributes to reducing the gender imbalances in the labor market that the pandemic exposed and exacerbated. We provide a financial programming exercise that demonstrates that the plan is financially responsible under a reasonable fiscal rule. Four core ideas stand out from our analysis. Firstly, while public investment can be key to reigniting economic growth, it does not go very far in tackling structural weaknesses. Secondly, public spending in health can actually achieve this from two fronts: by beginning to build a universal access social protection system and by addressing gender imbalances in the labor market. Thirdly, focusing public discussion on social protection enables a broader approach to policy reform by including formal employment and productivity enhancing reforms, which are essential for the sustainability of a broad social protection system. Finally, we also show that the sector mix in public investment has an impact on employment results, both in terms of the volume of jobs generated and their gender composition.